2014
DOI: 10.1136/jnnp-2014-308773
|View full text |Cite
|
Sign up to set email alerts
|

Apraxia profile differentiates behavioural variant frontotemporal from Alzheimer's dementia in mild disease stages

Abstract: Praxis disturbances are important but under-represented diagnostic features in mild stages of AD and bvFTD. Apraxia screening tests are easily applicable diagnostic tools, which may support clinical diagnoses of both neurodegenerative diseases. The analysis of individual apraxia profiles can effectively facilitate differential diagnosis of AD and bvFTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…11 A more recent study found that patients with amnestic AD performed significantly worse than patients with bvFTD on tests of limb apraxia, examining both ideational and ideomotor gestures. 14 It is widely held that the left parietal lobe plays a central role in limb apraxia, originating in Leipmann's early model describing a posterior to anterior stream that converts mental images of actions into a motor response, 2 and subsequent models have equally attributed a central role to the left parietal regions. 1 15 In conjunction with apraxia, left parietal dysfunction produces a range of other cognitive symptoms, including deficits in reading, writing and arithmetic, and there is suggestion in the literature that these clinical features may also be of relevance to the diagnosis of dementia syndromes, particularly in the AD spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…11 A more recent study found that patients with amnestic AD performed significantly worse than patients with bvFTD on tests of limb apraxia, examining both ideational and ideomotor gestures. 14 It is widely held that the left parietal lobe plays a central role in limb apraxia, originating in Leipmann's early model describing a posterior to anterior stream that converts mental images of actions into a motor response, 2 and subsequent models have equally attributed a central role to the left parietal regions. 1 15 In conjunction with apraxia, left parietal dysfunction produces a range of other cognitive symptoms, including deficits in reading, writing and arithmetic, and there is suggestion in the literature that these clinical features may also be of relevance to the diagnosis of dementia syndromes, particularly in the AD spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that patients with typical amnestic AD and patients with bvFTD present with distinct apraxia profiles15: the former were shown to have pronounced deficits in imitation of hand and finger postures (CAS subscore 2.2), while imitation of face postures (CAS subscore 2.1) was spared. In contrast, patients with typical bvFTD had relatively preserved imitation of hand and finger postures but pronounced deficits in imitation of face postures 15. Therefore, we calculated a limb (CAS 2.2) minus face (CAS 2.1) functional score for differential diagnosis of AD versus FTD praxis impairment.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have demonstrated that patients with typical AD and patients with bvFTD present with distinct forms of praxis impairment 15. Apraxia denotes the inability to perform specific predefined actions or to carry out learnt and purposeful movements due to acquired brain lesions 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…As a higher‐order disorder of sensorimotor integration, apraxia is commonly seen in neurological diseases, such as Alzheimer disease (AD) and stroke, and may contribute to dementia diagnosis in early stages . Among subtypes of apraxia, ideomotor apraxia is believed to reflect an impaired action production system.…”
mentioning
confidence: 99%
“…A s a higher-order disorder of sensorimotor integration, apraxia is commonly seen in neurological diseases, such as Alzheimer disease (AD) and stroke, and may contribute to dementia diagnosis in early stages. [1][2][3][4][5][6] Among subtypes of apraxia, ideomotor apraxia is believed to reflect an impaired action production system. Due to insufficient conversion to execution of motor programming, individuals with ideomotor apraxia exhibit deficits in the spatial organization, timing, and sequencing of gestural movements.…”
mentioning
confidence: 99%